Assessing academic librarians’ awareness on the importance and knowledge of collection development policy in Nigeria - Yakubu, Buhari; Mohd Khalid, Yanti Idaya Aspura; Samsuddin, Samsul Farid (Malaysian Journal of Library and Information Science, 2022)
Despite the importance of collection development policy (CDP) in developing library collection, little has been written about the awareness and knowledge of those who are responsible for formulating, maintaining, and updating this policy, especially in Nigeria where collection development challenges seem to be rampant. Therefore, this study assesses Nigerian academic librarians’ awareness on the importance and knowledge of CDP and also determines whether academic librarians’ educational level and working experience influence their awareness on the importance and knowledge of CDP. The study employed a quantitative methodology using a survey research design. One hundred and thirty-six (I36) academic librarians were recruited from three selected academic libraries in the Northwestern zone of Nigeria using a random sampling method. A survey questionnaire developed based on the IFLA (2001) guideline for collection development policy was used to collect the data. Descriptive and Spearman correlational analyses were used to analyze the data. The findings of the study revealed that academic librarians had a high level of awareness on the importance and knowledge of CDP. The findings also revealed that academic librarians’ educational level influenced their awareness on the importance (p = .000) and knowledge of CDP (p = .009). However, academic librarians’ working experience did not influence their awareness on the importance (p = .100) and knowledge of CDP (p = .307). This study has contributed to the management of academic libraries by providing useful information on the importance and knowledge of CDP among academic librarians in Nigeria. The study suggests that various educational programs are necessary to continue to improve the awareness on the importance and knowledge of CDP among library professionals in Nigeria.